The Role of Planning in Minimizing the Negative Impacts of Global Climate Change - Hagen, Bjoern (2016)
Climate change is one of the most salient challenges to society, both today and in the near future. Considering the complexity, uncertainties, and scale of possible global climate change (GCC) impacts, there is agreement that urban planning has the capacity to facilitate the development and implementation of adaptation as well as mitigation strategies. The land use planning system provides a framework to reduce greenhouse gas emissions considerably by addressing central issues such as community design, transportation networks and use, and increasing development density. Planning can also play an important role in impacting public behavior, thus slowing the pace of GCC and allowing the development and implementation of adaptation measurements. The purpose of this article is to examine the important role of the planning profession in developing and successfully implementing mitigation and adaptation strategies. There is a growing sense that planning will receive increasing attention as an important policy instrument for addressing both the causes and impacts of climate change. This work also supports the argument that climate action plans can be a vital instrument in confronting the challenges of climate change and that planners need to be more involved in the development and implementation process of such plans.